2007
DOI: 10.1037/0096-1523.33.4.753
|View full text |Cite
|
Sign up to set email alerts
|

Initial scene representations facilitate eye movement guidance in visual search.

Abstract: What role does the initial glimpse of a scene play in subsequent eye movement guidance? In 4 experiments, a brief scene preview was followed by object search through the scene via a small moving window that was tied to fixation position. Experiment 1 demonstrated that the scene preview resulted in more efficient eye movements compared with a control preview. Experiments 2 and 3 showed that this scene preview benefit was not due to the conceptual category of the scene or identification of the target object in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

20
218
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 199 publications
(242 citation statements)
references
References 58 publications
20
218
1
Order By: Relevance
“…In line with previous research (e.g., Castelhano & Henderson, 2007;Võ & Henderson, 2010), all metrics indicated search for everyday objects from real-world scenes was more efficient when participants were presented with a scene preview than a mask preview.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In line with previous research (e.g., Castelhano & Henderson, 2007;Võ & Henderson, 2010), all metrics indicated search for everyday objects from real-world scenes was more efficient when participants were presented with a scene preview than a mask preview.…”
Section: Discussionsupporting
confidence: 89%
“…First, a major component of how the scene-context guides search is that observers learn the spatial relationships between scenes and the objects within (Castelhano & Henderson, 2007;Castelhano & Heaven, 2010). As a result, the scene-context can guide search towards likely target locations, even when targets were not present in previews.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The HEOG measurements, however, were sensitive enough to detect a significant operand order effect. It should be noted that previous studies have also shown dissociations between behavioural data and eye movement data (e.g., Castelhano & Henderson, 2007). For example, Castelhano and Henderson recorded eye movements to explore whether the information acquired from a scene in an initial glimpse can facilitate subsequent eye movements, and they found significant effects in eye movement data, but not in reaction time data.…”
mentioning
confidence: 96%